(untitled) (Research, Society and Development, 2022)
Goat milk has been used for decades as a substitute for other milks because it is associated with better digestibility, lower allergenicity and potential health benefits to the consumer. The dairy industry occasionally discards by-products such as goat milk whey, a yellowish liquid that can be obtained by cheesemaking or by acid precipitation of caseins. Whey is the soluble fraction of milk that contains several notoriously interesting remaining components, such as proteins, present in the form of a protein pool, which have the potential to exhibit different biological activities as well as technological properties of great interest. The hydrolysis of goat whey proteins has proven to be an effective process to obtain bioactive molecules that due to their functionality have great potential to be microencapsulated. Thus, this literature review compiles only studies involving goat milk, and summarizes the composition of goat milk and the development of goat dairy farming. As well as seeks to emphasize the proteins and peptides of goat milk whey and the bioactivities to which they are related, in order to generate a greater understanding of their technological characteristics, biological and functional activities enabling gathering knowledge of a protein source with several health benefits that is usually discarded, and can be better used by the industry, providing income generation for those who survive this agricultural activity.